The Microstructure And Mechanical Properties Of The AlSi17Cu5 Alloy After Heat Treatment - Piątkowski J.; Matuła T. (Archives of Metallurgy and Materials, 2015)
In the paper results of the microstructure and mechanical properties (HB, Rm and R0,2) of AlSi17Cu5 alloy, subjected by solution heat treatment (500ºC/6h/woda) and aging (200ºC/16h/piec) are presented. In next step the alloy was modified and heated significantly above the Tliq temperature (separately and together). It was found that the increase in the strength properties of the tested alloy after heat treatment compared to alloys without solution heat treatment and aging was due to precipitation hardening. The applied aging treatment of ingots (preceded by solution heat treatment), causes not only increase in concentration in α(Al) solid solution, but also a favorable change of the primary Si crystals morphology. During stereological measurements significant size reduction and change in the morphology of hypereutectic silicon crystals ware found. This effects can be further enhanced by overheating the alloy to a temperature of 920ºC and rapid cooling before casting of the alloy.